RNF168 facilitates oestrogen receptor ɑ transcription and drives breast cancer proliferation. Issue 9 (5th July 2018) - Liu, Zhenhua; Zhang, Jinghang; Xu, Juntao; Yang, Huijie; Li, Xin; Hou, Yingxiang; Zhao, Yan; Xue, Min; Wang, Beibei; Yu, Na; Yu, Sifan; Niu, Gang; et al.
Abstract: Oestrogen receptor ɑ (ERɑ) is overexpressed in two‐thirds of all breast cancers and involves in development and breast cancer progression. Although ERɑ‐positive breast cancer could be effective treated by endocrine therapy, the endocrine resistance is still an urgent clinical problem. Thus, further understanding of the underlying mechanisms ERɑ signalling is critical in dealing with endocrine resistance in breast cancer patients. MCF‐7 and T47D breast cancer cell lines are used to carry out the molecular biological experiments. Western blot is used to assess the relative protein level of ERɑ, RNF168 and actin. Real‐time PCR is used the measure the relative ERɑ‐related gene mRNA level. Luciferase assay is used to measure the relative ERɑ signalling activity. Chromatin immunoprecipitation is used to measure the RNF168 binding affinity to ERɑ promoter regions. WST assay and flow cytometry are used to measure the cell proliferation capacity. We use Student's t test and one‐way ANOVA test for statistical data analysis. Here, we report an important role in ERɑ‐positive breast cancer cells for RNF168 protein in supporting cell proliferation by driving the transcription of ERɑ. RNF168 is highly expressed in breast cancer samples, compared with normal breast tissue. In patients with breast cancer, RNF168 expression level is correlated with poor endocrine treatment outcome. Depletion of RNF168 causes decreased cell proliferation in MCF‐7 and T47D cells. Besides, depletion RNF168 reduced mRNA level of ERɑ and its target genes, such as PS2 and GREB1. Chromatin immunoprecipitation revealed that ERɑ transcription is associated with RNF168 recruitment to ERɑ promoter region, suggesting that transcriptional regulation is one mechanism by which RNF168 regulates ERɑ mRNA level and ERɑ signalling in breast cancer cells. RNF168 is required for ERɑ‐positive breast cancer cell proliferation and facilitate ERɑ signalling activity possibly through promoting transcription of ERɑ.